The Distributional Welfare Effects of Rising Prices in the United States: The 1970's Experience - Stoker, Thomas M. (American Economic Review, 1986)
This paper presents estimates of the distributional welfare impacts of the actual price rises of energy and nonenergy commodities during the 1970-80 decade in the United States. Measures of welfare change based on net compensating variations are computed for different types of families. These show that welfare differences due to changes in commodity prices are minor compared to welfare differences due to different income growth patterns over the decade.